Association between vitamin B6 status and liver fibrosis: evidence from NHANES 2005–2010 - Peng, Junlu; Zhang, Wenjun; Pan, Meng; Yu, Yuanlin; Chen, Xiaopeng (Frontiers in Nutrition, 2025)
IntroductionLiver fibrosis (LF) is a chronic liver disease with an increasing global prevalence, caused by various underlying factors. Vitamin B6 is significantly altered during inflammation and has been associated with diabetes and hypertension. To date, no study has explored the association between vitamin B6 and LF. We aimed to explore the association between vitamin B6 metabolites—4-pyridoxine acid (4-PA), pyridoxal 5′-phosphate (PLP), and the 4-PA/PLP ratio (an indicator of vitamin B6 metabolism rate in the body)—and LF risk.MethodsData were extracted from the National Health and Nutrition Examination Surveys 2005–2010. Serum levels of 4-PA, PLP, and the 4-PA/PLP ratio were used to assess vitamin B6 status. The LF score was used to assess LF. Univariate and multivariate logistic regression tests were performed to explore the association between the vitamin B6 status and LF, using odds ratios (ORs) and 95% confidence intervals (CIs). Subgroup analysis based on age, obesity, and several complications was also conducted.ResultsOf the 8,063 subjects, 741 (9.19%) had LF. After adjusting all covariates, we observed that a high PLP level was associated with a lower risk of liver fibrosis (OR = 0.44, 95% CI: 0.35–0.56, p < 0.001), while a high 4-PA/PLP ratio was associated with a higher risk of liver fibrosis (OR = 2.69, 95% CI: 1.87–3.86, p < 0.001). No significant association was found between 4-PA and LF. All of these associations remained robust in each subgroup based on age, obesity, as well as hypertension, hyperlipidemia, diabetes, and cardiovascular disease.ConclusionIn conclusion, a high serum PLP level was associated with lower odds of LF, whereas a high 4-PA/PLP ratio, representing an increased metabolic rate of vitamin B6, was associated with higher odds of LF.